Purification of Legionella pneumophila major outer membrane protein and demonstration that it is a porin. - Gabay, J E (1985)
We have purified the major outer membrane protein (MOMP) of Legionella pneumophila, determined that it is associated with peptidoglycan, and characterized it as a porin. To purify the MOMP, we used a simple, rapid, three-step procedure that gave us the protein in high yield. The first step of the purification procedure involved selectively extracting the MOMP from whole bacterial cells with calcium and zwitterionic detergent. The second and third steps achieved purification by ion-exchange and molecular-sieve chromatography. The dissociation of the MOMP into monomers was dependent upon the presence of a reducing agent and was enhanced by treatment at 100 degrees C. To study the relationship of the MOMP to peptidoglycan, we extracted the protein by a modification of the Rosenbusch procedure. Like the Escherichia coli porins, the MOMP was peptidoglycan associated. The MOMP was at least partially dissociated from peptidoglycan in sodium dodecyl sulfate and a high salt concentration. To study the ion channel-forming properties of the MOMP, we reconstituted the MOMP in planar lipid membranes. The MOMP formed ion-permeable channels with a single-channel conductance size of 100 picoSiemens. The MOMP channels exhibited a fourfold selectivity for cations over anions and voltage-independent gating. These findings demonstrate that the MOMP is a porin with properties similar to those of E. coli porins.